Posterior capsule opacification rate after phacoemulsification in pediatric cataract: Hydrophilic versus hydrophobic intraocular lenses. Issue 10 (October 2019) - Sen, Pradhnya; Kshetrapal, Mansi; Shah, Chintan; Mohan, Amit; Jain, Elesh; Sen, Alok
Abstract : Purpose : To compare the rate of posterior capsule opacification (PCO) of hydrophilic acrylic intraocular lenses (IOLs) and hydrophobic acrylic IOLs in pediatric cataract surgery. Setting : Sadguru Netra Chikitsalaya, Chitrakoot, India. Design : Retrospective case series. Methods : The medical records of children who had uneventful cataract surgery with acrylic IOL implantation from 2010 to 2016 and a follow‐up of at least 1‐year were reviewed. The patients had implantation of a hydrophilic IOL (Ocuflex ANU6 IOL) or a hydrophobic IOL (AcrySof SA60AT). The main outcome measure was the PCO rate at the last follow‐up. Results : The study comprised 103 eyes (80 children). The mean age was 8.2 years ± 4 (SD) in the hydrophilic group (51 eyes) and 6.9 ± 4 years in the (52 eyes) hydrophobic group ( P = .1). The mean follow‐up was 38.8 months and 39.4 months, respectively. When the posterior capsule was left intact, 39.3% of eyes in the hydrophilic group and 13.4% of eyes in the hydrophobic group developed PCO ( P = .03). When primary posterior capsulotomy (PPC) and anterior vitrectomy were performed, 4.3% and 6.8%, respectively, developed PCO ( P = .69). Kaplan‐Meier survival plots with stratification for type of procedure (ie, PPC and anterior vitrectomy) showed a survival (ie, no PCO formation at 5‐year follow‐up) rate of 95.4% in the hydrophobic group and 88.8% in the hydrophilic group. Conclusion : Hydrophilic acrylic IOLs and hydrophobic acrylic IOLs implanted in the bag had comparable visual and surgical outcome and an equal rate of PCO formation when PPC and anterior vitrectomy were performed.